The Global Family Planning Revolution : Three Decades of Population Policies and Programs - Robinson, Warren C.; Ross, John A. (Washington, DC: World Bank, 2012)
This volume helps fill the gap left from insufficiently archived details of family planning programs carried out in many developing countries from the 1950s through the 1980s of their operations, their commonalities, and their differences, with much useful information and informed analysis. The programs were complex undertakings in difficult settings that had little prior experience to draw upon. Not surprisingly, as the case studies described here demonstrate, no single strategy was available that could be employed across these diverse situations, and procedures that were successful in one country did not necessarily function well in another. The case studies also indicate that developing a successful program was as much an art as a science. The key ingredient was being able to distinguish when a somewhat radical new approach was needed and when only some fine-tuning was necessary. While not a focus of this book, the family planning programs had several important, indirect effects on the field of population studies that merit attention as part of the record. First, uncertainty about the programs' worth and how to measure the extent of their success spurred a great deal of research on the measuring and modeling of fertility and contraceptive practice, on fecundity issues, on the effect of marriage patterns on fertility, and on a host of related topics. Second, the programs greatly advanced the science of evaluation. Third, the programs led demographers to work with specialists from many other disciplines, including public health, economics, sociology, political science, and psychology. Finally, the family planning efforts attracted many new and talented people to the field of population studies. The 23 case studies presented here were the earliest national efforts to establish organized family planning programs for entire populations. The resulting chapters naturally vary in terms of their balance of history, analysis, and personal reflections given the wide diversity of national contexts and program types. The study's overall conclusion is that, for the most part, the family planning program "experiment" worked: policy and program interventions contributed substantially to the revolutionary rise of contraceptive use and to the decline in fertility that has occurred in the developing world in the past three decades.